Does mental practice still enhance performance? A 24 Year follow-up and meta-analytic replication and extension - Toth, A. J.; McNeill, E.; Hayes, K.; Moran, A. P.; Campbell, M. (Psychology of Sport and Exercise, 2020)
Objectives: Motor imagery (MI) is a dynamic mental state during which the representation of a given motor movement is rehearsed in working memory without overt motor output. Mental practice (MP; also known as motor imagery practice) is the systematic application of MI for the cognitive rehearsal of a task in the absence of overt physical movements. Although MP is known to enhance skilled performance, debate still exists about the magnitude and moderators of these imagery effects. Against this background, and amid concerns about the "reproducibility crisis" in psychology, it seems timely to revisit, update and extend a key meta-analysis of MP effects published over two decades ago - namely, that of Driskell, Copper, and Moran (1994). To this end, the present paper reports a methodological replication of the Driskell et al`s (1994) meta-analysis of MP effects.